The Influence of Price Perception and Product Completeness on Sales of Goods at PT Segar Harum Kalimantan Bontang Branch - Sari, Ayu Dita; Agustin Prasetyawati; Dorliana Sihombing (Universitas Muhammadiyah Palu, 2024)
This research was conducted to determine the influence of price perception and product completeness on sales of goods at PT Segar Harum Kalimantan Bontang Branch. This research is a type of quantitative research. The respondents in this research were 100 consumers who shopped at PT Segar Harum Kalimantan Bontang Branch. Data was processed using SPSS version 16.0. The results were tested using multiple regression analysis, F test, t test and R2 test. In multiple linear regression testing, it was obtained that Y= 20.179 + 0.176X1 + 0.270X2. F calculation shows a value of 148.349 with a significance level of 0.000. Meanwhile, the F table value is 3.09. This shows that the calculated F value is > F table, namely 148.349 > 3.09 and the significance level is 0.000 < 0.05. Testing the tcount value for the price perception variable (X1) is greater than the ttable value (9.395 > 1.984) with a significance level below 0.05, namely 0.000. Meanwhile, the tcount value for the product completeness variable (X2) is greater than the ttable value (13.955 > 1.984) with a significance level below 0.05, namely 0.000. The obtained value of R Square = 0.754 = 75.4%. This means that the independent variables price perception and product completeness together influence the dependent variable sales of goods by 74.9% and the remaining 25.1% is influenced by other variables not included in this research. From these results it is shown that the perception of price and product completeness together have a significant effect on sales of goods at PT Segar Harum Kalimantan Bontang Branch